Produk Fashion Bagi Masyarakat Urban Indonesia Dengan Pemanfaatan Rempah Nusantara - Amanah Asri (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2022)
Indonesia is an agricultural country known for its rich natural resources, one of which is spices. Spices are commodities that have millions of benefits for human life, even spices can affect political, economic, and socio- culturalconditions on a global scale. Urban communities who come from various ethnicities to urban spaces have now realized that they still have elements of local wisdom that enrich the existence of urban communities towards a global and cosmopolitan society. The role of urban fashion by using clothes is a form of concern for cultural preservation. The use of natural fibers as a substitute for synthetic fibers in one of the wise steps in increasing the economic value of natural fibers considering the limitations of non-renewable natural resource. One of the natural sources used is fiber from citronella spice waste. How to use spice waste fiber is implemented for fashion products, so the researchers conducted a study in the utilization of citronella spice waste through qualitative research methods, art base research and semiotics by conducting a study of fiber morphology identification (stems and leaves) from spice waste. This study looks at the utilization of archipelago’s spice waste as a fashion product. The purpose of this research study is examined spices for fashion products. Reduce the impact of greenhouse gas production by managing spice waste, and empowering communities to realize sustainable development by managing spice waste into a resource that has benefits so that spice waste can be used as sustainable fashion.